2017
DOI: 10.3389/fmed.2017.00025
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intratumor Heterogeneity in Modern Pathology: A Multisite Tumor Sampling Perspective

Abstract: Current sampling protocols of neoplasms along the digestive tract and in the urinary bladder have to be updated, as they do not respond to the necessities of modern personalized medicine. We show here that an adapted version of multisite tumor sampling (MSTS) is a sustainable model to overcome current deficiencies in digestive and bladder tumors when they are large enough so as to make unaffordable a total sampling. The new method is based on the divide-and-conquer algorithm and includes a slight modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The intra-tumor heterogeneity is recognized as a process with great clinical importance and is related to pathological observation of different tumoral areas [24] associated with cancer progression, resistance to therapy, and recurrences [24,25]. In our study, we observed the heterogeneous morphological aspect of SPNP by gross and histopathological examinations.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The intra-tumor heterogeneity is recognized as a process with great clinical importance and is related to pathological observation of different tumoral areas [24] associated with cancer progression, resistance to therapy, and recurrences [24,25]. In our study, we observed the heterogeneous morphological aspect of SPNP by gross and histopathological examinations.…”
Section: Discussionmentioning
confidence: 61%
“…A recent report emphasizes the importance of histopathological and molecular analysis of different fragments of the same tumor to obtain a better detection of intra-tumoral heterogeneity [26]. Some authors have used this system in the evaluation of tumors of the urinary bladder, stomach and large bowel [24]. However, for pancreatic neoplasms and especially…”
Section: Discussionmentioning
confidence: 99%
“…In this particular setting, the anatomical barrier represented by the muscularis propria forces the tumors to grow with their long axes parallel to the wall of the viscera forming tumors with plate-like shapes and not like spheroids as happens in the kidney, liver or other solid organs. Instead of tissue cubes, the sampling model here gets tissue bars including the whole thickness (from the lumen to the perivisceral adipose tissue) of the viscera [45]. MSTS has obtained here also better performances in detecting ITH compared with routine sampling [45].…”
Section: The Need For An Updated Tumor Sampling Adapted To Tumor Typementioning
confidence: 99%
“…Instead of tissue cubes, the sampling model here gets tissue bars including the whole thickness (from the lumen to the perivisceral adipose tissue) of the viscera [45]. MSTS has obtained here also better performances in detecting ITH compared with routine sampling [45].…”
Section: The Need For An Updated Tumor Sampling Adapted To Tumor Typementioning
confidence: 99%
“…In this particular setting, the anatomical barrier represented by the muscularis propria leads the tumors to grow with their long axes parallel to the wall of the viscera forming tumors with plate-like shapes, and not like spheroids as happens in the kidney, liver or other solid organs. Instead of tissue cubes, the sampling model here gets tissue bars including the whole thickness (from the lumen to the perivisceral adipose tissue) of the viscera [53]. MSTS has obtained here also better performances in detecting ITH compared with routine sampling [53].…”
Section: The Need For An Updated Tumor Sampling Adapted To Tumor Typementioning
confidence: 99%